PENGARUH BRAND IMAGE DAN E- SERVICE QUALITY TERHADAP CUSTOMER SATISFACTION SERTA LOYALITAS PENGGUNA APLIKASI GOJEK DI TABANAN - I Gusti Ngurah Khrisna Siwa Putra; Luh Komang Candra Dewi (Universitas Triatma Mulya, 2020)
This study aims to analyze the effect of brand image on customer satisfaction, the effect of e-service quality on customer satisfaction, the influence of brand image on loyalty, the influence of e-service quality on loyalty, the influence of customer satisfaction on the loyalty of Gojek application users in Tabanan. The respondents of this study were 70 people who used the Gojek application in Tabanan. The hypothesis test used is bootstrap resampling in SEM PLS. The analysis shows that: 1) Brand image has a positive and significant effect on customer satisfaction. 2) Brand image has a positive and significant effect on loyalty. 3) customer satisfaction has a positive and significant effect on customer loyalty. 4) E-service quality has a positive and significant effect on Customer satisfaction. 5) E-service quality does not significantly influence the loyalty of Gojek application users in Tabanan. The study gives consideration to the leadership of PT. Karya Anak Bangsa application or called Gojek to improve brand image so that users of the Gojek application in Tabanan increase their satisfaction.Keywords: brand image, e-service quality, customer satisfaction, loyalty.